Answers

2015-09-15T00:38:24+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
From the equations of kinematics we have that :  s= u t + 1/2 a t²

  Displacement during the first n sec,     = S_n = u * n + 1/2 * a * n²
  Displacement during the first n-1 sec.  = S_n-1 = u * (n-1) + 1/2 * a * (n-1)²
 
  displacement during n th sec. = S_n - S_n-1
       = u n + 1/2 a n² - u n + u - 1/2 a n² + 1/2 a * 2n - 1/2 a * 1
       = u + a ( n - 1/2)

that is the answer.

1 5 1
click on thanks button above pls
select best answer pls